Gastrointestinal helminths of Gentoo penguins (Pygoscelis papua) from Stranger Point, 25 de Mayo/King George Island, Antarctica - Diaz, Julia Inés; Fusaro, Bruno; Longarzo, Maria Lucrecia; Coria, Néstor Rubén; Vidal, Virginia; Jerez, Silvia; Ortiz, Juana; Barbosa, Andrés (Parasitology Research)
The aim of this work is to contribute to the knowledge of gastrointestinal parasites of the Gentoo penguin (Pygoscelis papua) from 25 de Mayo/King George Island (South Shetlands, Antarctica). Gastrointestinal tracts of 37 fresh dead individuals (21 chicks, 10 juveniles, and 6 adults) were collected from December 2006 to February 2012 and examined for macroparasites. Four adult parasite species were found: one Cestoda species (Parorchites zederi), two Nematoda species (Stegophorus macronectes and Tetrameres wetzeli), and one Acanthocephalan (Corynosoma shackletoni). Two species of immature acanthocephalans, Corynosoma hamanni and Corynosoma bullosum, were found in a single host. This is the first record of Tetrameres wetzeli in Gentoo penguins. The low parasite richness observed could be related to the stenophagic and pelagic diet of this host species which feeds almost exclusively on krill. Fil: Diaz, Julia Inés. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico La Plata. Centro de Estudios Parasitológicos y de Vectores (i); Argentina. Universidad Nacional de La Plata; Argentina Fil: Fusaro, Bruno. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico La Plata. Centro de Estudios Parasitológicos y de Vectores (i); Argentina. Universidad Nacional de La Plata; Argentina Fil: Longarzo, Maria Lucrecia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico La Plata. Centro de Estudios Parasitológicos y de Vectores (i); Argentina. Universidad Nacional de La Plata; Argentina Fil: Coria, Néstor Rubén. Instituto Antártico Argentino. Departamento Biología de Predadores Tope; Argentina Fil: Vidal, Virginia. Universidad de Murcia; España Fil: Jerez, Silvia. Universidad de Murcia; España Fil: Ortiz, Juana. Universidad de Murcia; España Fil: Barbosa, Andrés. Museo Nacional de Ciencias Naturales. Departamento de Ecología Evolutiva; España. Consejo Superior de Investigaciones Cientificas; España